Cell Division Control Protein 42 Interacts With Hepatitis E Virus Capsid Protein and Participates in Hepatitis E Virus Infection - Fan, Mengnan; Luo, Yuhang; Zhang, Beibei; Wang, Jiaxi; Chen, Tianxiang; Liu, Baoyuan; Sun, Yani; Nan, Yuchen; Hiscox, Julian A.; Zhao, Qin; Zhou, En-Min (Frontiers in Microbiology, 2021)
Hepatitis E Virus (HEV) causes viral hepatitis in humans worldwide, while a subset of HEV species, avian HEV, causes hepatitis-splenomegaly syndrome in chickens. To date, there are few reports on the host proteins interacting with HEV and being involved in viral infection. Previous pull-down assay combining mass spectrometry indicated that cell division control protein 42 (CDC42), a member belonging to the Rho GTPase family, was pulled down by avian HEV capsid protein. We confirmed the direct interaction between CDC42 and avian and mammalian HEV capsid proteins. The interaction can increase the amount of active guanosine triphosphate binding CDC42 state (GTP-CDC42). Subsequently, we determined that the expression and activity of CDC42 were positively correlated with HEV infection in the host cells. Using the different inhibitors of CDC42 downstream signaling pathways, we found that CDC42-MRCK (a CDC42-binding kinase)-non-myosin IIA (NMIIA) pathway is involved in naked avian and mammalian HEV infection, CDC42-associated p21-activated kinase 1 (PAK1)-NMIIA/Cofilin pathway is involved in quasi-enveloped mammalian HEV infection and CDC42-neural Wiskott-Aldrich syndrome protein-actin-polymerizing protein Arp2/3 pathway (CDC42-(N-)WASP-Arp2/3) pathway participates in naked and quasi-enveloped mammalian HEV infection. Collectively, these results demonstrated for the first time that HEV capsid protein can directly bind to CDC42, and non- and quasi-enveloped HEV use different CDC42 downstream signaling pathways to participate in viral infection. The study provided some new insights to understand the life cycle of HEV in host cells and a new target of drug design for combating HEV infection.